Development of mobile application-based digital drama for Arabic language to improve students’ vocabulary - Nurul Azni Mhd Alkasirah; Mariam Mohamad; Mageswaran Sanmugam; Girija Ramdas (Journal of Education and Learning (EduLearn), 2026)
The Arabic language is one of the foreign languages offered in Malaysian education. In Arabic, learning vocabulary is particularly important because it forms the foundation of language acquisition. However, past research showed that a large number of Malaysian students struggle with understanding and memorizing Arabic vocabulary because they are unfamiliar with it. Thus, this research focuses on developing an appropriate mobile application that will support Malaysian religious secondary school students in improving their mastery of Arabic vocabulary. This study attempts to create a mobile application-based digital drama by adopting the analyze, design, develop, implement, and evaluate (ADDIE) model. The ADDIE model was integrated as a structured approach for producing educational material that is both enjoyable and beneficial to students. Six subject matter experts were invited to evaluate the effectiveness of the mobile application-based digital drama. Based on the validation results and feedback obtained, it can be concluded that mobile application-based digital drama was valid and effective with high scores for format and graphic suitability to be utilized as an instructional tool for learning Arabic vocabulary among Malaysian religious secondary school students.